Expanding the agenda for addressing mistreatment in maternity care: a mapping review and gender analysis - Myra L. Betron; Tracy L. McClair; Sheena Currie; Joya Banerjee (BMC, 2018)
Abstract Background This paper responds to the global call to action for respectful maternity care (RMC) by examining whether and how gender inequalities and unequal power dynamics in the health system undermine quality of care or obstruct women's capacities to exercise their rights as both users and providers of maternity care. Methods We conducted a mapping review of peer-reviewed and gray literature to examine whether gender inequality is a determinant of mistreatment during childbirth. A search for peer-reviewed articles published between January 1995 and September 2017 in PubMed, Embase, SCOPUS, and Web of Science databases, supplemented by an appeal to experts in the field, yielded 127 unique articles. We reviewed these articles using a gender analysis framework that categorizes gender inequalities into four key domains: access to assets, beliefs and perceptions, practices and participation, and institutions, laws, and policies. A total of 37 articles referred to gender inequalities in the four domains and were included in the analysis. Results The mapping indicates that there have been important advances in documenting mistreatment at the health facility, but less attention has been paid to addressing the associated structural gender inequalities. The limited evidence available shows that pregnant and laboring women lack information and financial assets, voice, and agency to exercise their rights to RMC. Women who defy traditional feminine stereotypes of chastity and serenity often experience mistreatment by providers as a result. At the same time, mistreatment of women inside and outside of the health facility is normalized and accepted, including by women themselves. As for health care providers, gender discrimination is manifested through degrading working conditions, lack of respect for their abilities, violence and harassment,, lack of mobility in the community, lack of voice within their work setting, and limited training opportunities and professionalization. All of these inequalities erode their ability to deliver high quality care. Conclusion While the evidence base is limited, the literature clearly shows that gender inequality-for both clients and providers-contributes to mistreatment and abuse in maternity care. Researchers, advocates, and practitioners need to further investigate and build upon lessons from the broader gender equality, violence prevention, and rights-based health movements to expand the agenda on mistreatment in childbirth and develop effective interventions.